Diversity and longitudinal distribution of freshwater fish in Klawing River, Central Java, Indonesia - SUHESTRI SURYANINGSIH; SRI SUKMANINGRUM; SORTA BASAR IDA SIMANJUNTAK; KUSBIYANTO KUSBIYANTO (Biodiversitas Journal of Biological Diversity, 2018)
Suryaningsih S, Sukmaningrum S, Simanjuntak SBI, Kusbiyanto. 2018. Diversity and longitudinal distribution of freshwater fish in Klawing River, Central Java, Indonesia. Biodiversitas 19: 85-92. The aims of this study were to evaluate the diversity and longitudinal distribution of fish in Klawing River, Purbalingga (Central Java). The survey was performed using a clustered random-sampling technique. The river was divided into upstream, midstream and downstream regions. Species diversity was measured as the number of species, and the longitudinal distribution was assessed by determining the fish species present in each of the three regions. Eighteen fish species of eleven families were identified in the Klawing River: Cyprinidae, Bagridae, Mastacembelidae, Anabantidae, Cichlidae, Channidae, Eleotrididae, Beleontinidae, Osphronemidae, Poecilidae, and Siluridae. Cyprinidae exhibited the highest number of species (six), followed by Bagridae and Cichlidae (two species each). The other families were represented by one species each. A single cluster analysis showed that the upstream population had a similarity of 78% and 50% with the midstream and downstream populations, respectively. Species and family diversities were higher in the midstream populations than in the upstream and downstream populations. This longitudinal distribution may be due to differences in environmental conditions and suggests that management of the land surrounding the Klawing River is a key factor in the conservation of freshwater fish.